Effect of fiber orientation on fracture toughness of laminated composite plates [0°/?°]s - Kaman, Mete Onur (Pergamon-Elsevier Science Ltd, 2011)
Fracture toughness of single edge notched fiber reinforced composite plates is investigated experimentally. Load-displacement curves for unidirectional carbon fiber/epoxy resin reinforced composite plates are obtained experimentally under tensile load. Fracture toughness is obtained by determining failure loads. For numerical study. ANSYS is used. Material properties of laminates are calculated with classical laminated plate theory and applied to the finite element model by using plane element. Stiffness matrix of laminates is determined and shell element is chosen for numerical solution. Critical stress intensity factors are calculated with Displacement Correlation Method under experimental failure load conditions. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Laminated composites; Displacement Correlation Method; Finite element analysis; Fracture toughness; Stress intensity factor